Trunk posture and statico-dynamical spine analysis - comparing ultrasound based vs. optically based measurement system - Thorwesten, L.; Schneiders, D.; Schilgen, M.; Völker, K. (ISBS - Conference Proceedings Archive (Konstanz), 2009)
The purpose of this study was to compare two different methods measuring trunk posture and statico-dynamical spine analysis. 32 patients participated in this cross sectional study. Comparing measured values a wide congruence could be demonstrated with marginal underestimating in kyphosis and lordosis data for the ultrasound based system. The largest deviation could be shown for pelvic obliquity measured in mm. Trunk inclination, vertical deflection and pelvic obliquity measured in degree showed proper analogy for both measuring systems. Validity, reliability based on particular technical principles could be verified.